ANALISIS PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI BMT NUANSA UMAT JATIM PAMEKASAN - Reza Mubarak; Asep Maulana; Umarul Faruq (Reinforce: Journal of Sharia Management, 2023)
The Islamic Economic System prohibits usury (riba) and the unfair accumulation of wealth by specific parties. In practical terms, there is a need for widespread dissemination regarding various products, services, the fundamental principles of the relationship between financial institutions and customers, and the permissible ways of conducting business in Islamic finance. Employee performance and productivity are crucial factors for the success of financial institutions. Proper and effective human resource management can enhance employee performance and enable the achievement of company goals. This research aims to determine the influence of the work environment and work motivation on employee performance at BMT NU Jatim in the Pamekasan Regency. The research methodology employs a quantitative approach with a population of 58 individuals, and a saturated sampling technique is used to select the sample. The primary data used in this study are collected through questionnaires. The data analysis technique employed is multiple linear regression analysis. The analysis results indicate that the work environment has a positive and significant impact on employee performance, as does work motivation.